2015
DOI: 10.1177/0040517515592815
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-regulated sheath/core submicron fiber with poly(diethylene glycol hexadecyl ether acrylate) as a core

Abstract: Side-chain crystallizable comb-like polymers can be used as polymeric thermal energy-storage materials. Diethylene glycol hexadecyl ether acrylate (C16E2AA) was synthesized with sodium alkoxide using diethylene glycol hexadecyl ether (C16E2) and acryloyl chloride as reactants. C16E2AA was prepared by free radical polymerization to form a comb-like polymeric phase change material, poly(diethylene glycol hexadecyl ether acrylate) (PC16E2AA). A series of sheath/core composite submicron fibers were coaxially elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…There are three diffraction peaks in the WAXD pattern of cellulose, whose locations are 14.8°, 16.4°, and 22.6°, and the d-spacings are 0.60 nm, 0.54 nm, and 0.39 nm, respectively. E 2 C 16 shows two sharp peaks centered at 21.2° and a small peak centered at 23.7°, with d-spacings of 0.42 nm and 0.38 nm, and the crystal type of E 2 C 16 is hexagonal [18]. It is reported that the characteristic diffraction peaks (110) and (020) of cellulose II are locate at 19.9° and 22.1° [19].…”
Section: Resultsmentioning
confidence: 99%
“…There are three diffraction peaks in the WAXD pattern of cellulose, whose locations are 14.8°, 16.4°, and 22.6°, and the d-spacings are 0.60 nm, 0.54 nm, and 0.39 nm, respectively. E 2 C 16 shows two sharp peaks centered at 21.2° and a small peak centered at 23.7°, with d-spacings of 0.42 nm and 0.38 nm, and the crystal type of E 2 C 16 is hexagonal [18]. It is reported that the characteristic diffraction peaks (110) and (020) of cellulose II are locate at 19.9° and 22.1° [19].…”
Section: Resultsmentioning
confidence: 99%
“…Increasing greenhouse gas emissions and fossil fuel consumption fueled the exploration of more efficient renewable energy sources [1,2]. Effective energy storage devices and systems are critical to increasing energy adequacy and reducing time and space mismatches in energy supply and demand, thereby reducing environmental impact [3,4,5,6]. Energy savings could be realized by thermal energy storage systems that use phase change materials (PCMs) [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The first comb-like polymers, poly(n-alkyl acrylate)s, were synthesized by Fisher [6] using the radical polymerization method. Since then, poly(n-alkyl methacrylate)s, poly(n-alkyl vinyl ester)s, poly(n-alkyl vinyl ether)s, poly(n-alkyl acrylamide)s, poly(n-alkyl ethylene)s, poly(n-alkyl ethylene oxide)s, poly(polyethylene glycol octadecyl ether methacrylate), poly(diethylene glycol hexadecyl ether acrylate), and poly(n-alkyl itaconate)s [7][8][9][10][11][12] were synthesized in succession. These reports about comb-like polymers with different topologies, rigidity degrees of main chains, and the length scale of Liu et al [13] prepared a series of shape-stabilized comb-like polymeric phase change materials (poly(ethylene-graft-maleic anhydride)-g-alkyl alcohol) by the esterification reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The melting and crystallizing enthalpy of poly(C 18 E 2 MMA) were 73 and 81 J/g, respectively, which started to melt at 41.1 • C and crystallize at 35.4 • C. Zhang et al [7] synthesized diethylene glycol hexadecyl ether acrylate (C 16 E 2 AA), and then poly(diethylene glycol hexadecyl ether acrylate) (PC 16 E 2 AA) was prepared by free radical polymerization. PC 16 E 2 AA melted at 33.8 • C and crystallized at 25.8 • C, and the melting and crystallizing enthalpy were 90 and 85 J/g, respectively.…”
Section: Introductionmentioning
confidence: 99%